Super-Toughened Poly(lactic Acid) with Poly(ε-caprolactone) and Ethylene-Methyl Acrylate-Glycidyl Methacrylate by Reactive Melt Blending - Hou, Ao-Lin (Polymers (Basel), 2019)
In recent years, poly(lactic acid) (PLA) has attracted more and more attention as one of the most promising biobased and biodegradable polymers. However, the inherent brittleness significantly limits its wide application. Here, ternary blends of PLA, poly(ε-caprolactone) (PCL) with various amounts of ethylene-methyl acrylate-glycidyl methacrylate (EMA-GMA) terpolymer were fabricated through reactive melt blending in order to improve the toughness of PLA. The effect of different addition amounts of EMA-GMA on the mechanical properties, interfacial compatibility and phase morphology of PLA/PCL blends were studied. The reactions between the epoxy groups of EMA-GMA and carboxyl and hydroxyl end groups of PLA and PCL were investigated thorough a Fourier transform infrared (FT-IR). The miscibility and thermal behavior of the blends were studied through a dynamic mechanical analysis (DMA), differential scanning calorimetric (DSC) and X-ray diffraction (XRD). The phase morphology and impact fracture surface of the blends were also investigated through a scanning electron microscope (SEM). With the addition of 8 phr EMA-GMA, a PLA/PCL (90 wt %:10 wt %)/EMA-GMA ternary blend presenting a suitable multiple stacked phase structure with an optimum interfacial adhesion exhibited an elongation at break of 500.94% and a notched impact strength of 64.31 kJ/m(2) with a partial break impact behavior. Finally, the toughening mechanism of the supertough PLA based polymers have been established based on the above analysis.